2021
DOI: 10.1111/ajt.16488
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 7 releasing particles enhance islet engraftment and improve metabolic control following islet transplantation in mice with diabetes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Modulation of the liver niche with growth factors [109] and anti-inflammatory agents [110] have been used with some success and polymer properties may be exploited to regulate release of such factors when islets are immediately transplanted and particularly vulnerable to apoptosis [109,111], but these are still at a very early pre-clinical stage. Accelerating the vascularisation of transplanted islets with a number of approaches including gene therapy methods [112] may be a relevant strategy to accelerate islet engraftment and may improve transplantation outcomes.…”
Section: Therapies In Early Clinical Trials and On The Horizonmentioning
confidence: 99%
“…Modulation of the liver niche with growth factors [109] and anti-inflammatory agents [110] have been used with some success and polymer properties may be exploited to regulate release of such factors when islets are immediately transplanted and particularly vulnerable to apoptosis [109,111], but these are still at a very early pre-clinical stage. Accelerating the vascularisation of transplanted islets with a number of approaches including gene therapy methods [112] may be a relevant strategy to accelerate islet engraftment and may improve transplantation outcomes.…”
Section: Therapies In Early Clinical Trials and On The Horizonmentioning
confidence: 99%
“…56 Alwahsh et al transplanted islets with FGF7-loaded galactosylated poly (DL-lactide-co-glycolic acid) particles into diabetic mice via the hepatic portal vein and found that these particles display a good safety profile and are able to induce short-term hepatocyte proliferation, enhance islet implantation, normalize blood glucose levels and improve liver damage. 57…”
Section: Fgf7: a Novel Materials To Enhance Islet Implantationmentioning
confidence: 99%
“…56 Alwahsh et al transplanted islets with FGF7-loaded galactosylated poly (DLlactide-co-glycolic acid) particles into diabetic mice via the hepatic portal vein and found that these particles display a good safety profile and are able to induce short-term hepatocyte proliferation, enhance islet implantation, normalize blood glucose levels and improve liver damage. 57 FGF9: a contributing factor to MAFLD-HCC FGF9 is highly expressed in adipose tissue and moderately expressed in the liver. It promotes adipogenesis, aggravates inflammation, and promotes WAT development by inhibiting WAT browning.…”
Section: Fgf7: a Novel Materials To Enhance Islet Implantationmentioning
confidence: 99%
“…In this issue of AJT, Alwahsh et al 5 present their innovate strategy to precondition the liver transplant site by creating a proliferative environment to subsequently enhance mouse syngeneic islet engraftment in order to improve long-term graft function.…”
Section: Conditioning the Liver Into A Favorable Niche For Pancreatic Islet Engraftmentmentioning
confidence: 99%
“…In this issue of AJT , Alwahsh et al 5 present their innovate strategy to precondition the liver transplant site by creating a proliferative environment to subsequently enhance mouse syngeneic islet engraftment in order to improve long‐term graft function. To achieve liver tissue‐specific delivery of FGF, Alwahsh et al co‐transplanted syngeneic murine islets with FGF7 releasing galactosylated (GAL) poly(DL‐lactide‐co‐glycolic acid) particles.…”
mentioning
confidence: 99%